Development of audit checklist for Muslim-friendly hotel's room - Siti Syahirah binti Saffinee (International Institute for Halal Research and Training, International Islamic University Malaysia, 2017)
The concept of Muslim-friendly hotels has been discussed since 1982. However, although in Malaysia there are nearly 3000 hotels that contribute to a capacity of about 200,000 rooms, only less than 10% out of that are considered as Muslim-friendly. Consequently, this research sought to create an auditing checklist guideline for Muslim-friendly hotel rooms, which will lead to the understanding of the facilities, services, as well as its elements and requirements. There were three objectives for this research, namely to identify the Islamic elements for a Muslim-friendly hotel room in Malaysia, to develop the audit checklist for Muslim-friendly hotel rooms (AC-MFHR) in Malaysia, and to assess the existing Islamic elements in conventional hotel rooms and in self-proclaimed Muslim-friendly hotel rooms in Malaysia. The followed methodology was literature research, observation and expert reviewed discussions, which were triangulated for validation in qualitative research. By selecting eight hotels as samples, and involving two types of hotel managements, the findings revealed that there are significant differences in the compliance and non-compliance criteria with the Islamic elements in the hotel rooms. They indicated four categories, namely prayer amenities, entertainment, environment, and interior infrastructure. Additionally, there are sixteen Islamic elements for Muslim-friendly hotel rooms, namely adequate praying space, bed and toilet position, decoration, TV channel programming, hygiene and cleanliness, toilet fitted with a bidet shower, Kiblat pointing signage, Qur'an with translation, female prayer garment, information on prayer times, halal toiletries, mini bar, no consumption of non-halal food and beverages, the day and night curtain, and the workable system. Moreover, the extent and availability of existing hotel management of incorporating Muslim-friendly concepts are different. 77% of elements compliance was scored in 'self-proclaimed' Muslim-friendly hotels rooms, while conventional hotel rooms received less than 54% of elements compliance. Furthermore, this proposed AC-MFHR was verified through validation by reviewed discussions by experts. Therefore, the developed AC-MFHR has been identified as a key finding to standardise Islamic elements in facilities and services. The results will facilitate improvements in the hotel industry, especially for those who are interested in substituting their hotel management toward the concept of Muslim-friendly hotel rooms.